(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Magnolia, a genus comprising approximately 225 species of trees and shrubs in the family Magnoliaceae. Magnolia plants can be evergreen or deciduous and bear alternate smooth-margined leaves. In this paper six species of magnolia were studied based on morphological observations of taxonomically relevant traits. Among these, four species—Magnolia alba, Magnolia champaca, Magnolia grandiflora, and Magnolia liliifera—are previously documented, while two species, Magnolia figo, a 3–4 m tall shrub with a sweet banana scent, and Magnolia coco, are newly recorded additions to the flora of Bangladesh. This study focused on the leaf descriptions viz. average breadth and length, average size, fresh weight, and dry weight of leaves of the six species with their brief taxonomic description, morphology features, and identifiable pictures. In terms of relative average leaf size (RALS), Magnolia alba has the largest, while Magnolia figo has the smallest. M. champaca exhibits the highest water content, and M. coco has the highest dry matter percentage at approximately 47.03%. The conservation status of these species was evaluated, with four classified as Least Concern (LC) and two as Data Deficient (DD). The addition of Magnolia coco and Magnolia figo brings the total number of Magnolia species in Bangladesh to fourteen. Overall, this study on Magnolia will help future research projects, conservation efforts, and management activities by enhancing the understanding of the various uses of these species. J Bangladesh Agril Univ 22(2): 158-165, 2024